Associação de polimorfismos dos genes de citocinas com susceptibilidade para infecção por micobactérias - Nunes, Sammara Tavares (2010)
Cytokine genetic polymorphisms studies are helpful to determine diverse genetic profiles, to correlate populations, and to promote the knowledge of ethnic influence on the genetic susceptibility to diseases. The aim of the present study was to correlate TNF-α -308, TGF-β, codon 10 and codon 25, IL-10 -1082, -819, -592, IL-6 -174, and IFN-γ +874 polymorphisms with the susceptibility and the protection to M. tuberculosis and M. leprae infection. The study included 194 patients, 65 of them with leprosy and 129 with tuberculosis, and 168 healthy volunteers. The local Ethical Committee approved the study and all of the participants consented. To DNA purification and amplification 3-5 mL of peripheral blood was collected. An Easy-DNA (Invitrogen) kit was used to purification. Cytokines SNPs TNF-α (-308G>A), TGF-β codon 10 and 25, IL-10 (-1082G>A, -819C>T, -592C>A), IL-6 (-174G>C) and IFN-γ (+874T>A) were amplified by the polymerase chain reaction using sequence-specific primers (SSP-PCR) (One-Lambda). Statistical analysis was proceeded using GraphPad prism 5, and p values were determined by the Fisher test, with significance when p<0.05. Frequencies of TNFα genotypes were not different among patients and controls. However, IL-10 genotypes analyses showed a reduction on the frequency of the GCC/GCC in patients (7.1% vs 17.9%, p=0.006). This reduction was also observed with the IL-6 GC (22.1% vs 32.8%, p=0.04) and IFNγ TA (36.6% vs 51.6%, p=0.01) genotypes. In contrast, the frequencies of the IL-6 GG (72.1% vs 57.0%, p=0.008) and the IFNγ AA (54.0% vs 41.4%, p=0.03) genotypes were increased in patients. Furthermore, there was a trend to an increase in the frequency of the TGFβ CC/GC genotype (7.5% vs 0.8%, p=0.06). In conclusion, IL-10 (GCC/GCC), IL-6 (GC) and IFN-γ (TA) genotypes conferred protection against, while TGF-β (CC/GC), IL-6 (GG) and IFN-γ (AA) genotypes determined susceptibility to mycobacteria infection. On the other hand, T allele in codon 10 and G allele in codon 25 of the TGF-β gene, determined protection against tuberculosis. In contrast, the IL-6 -174G conferred susceptibility to mycobacteria infection.